2009
DOI: 10.1007/s00114-009-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Recilia banda Kramer (Hemiptera: Cicadellidae), a vector of Napier stunt phytoplasma in Kenya

Abstract: Napier grass (Pennisetum purpureum) is the most important fodder crop in smallholder dairy production systems in East Africa, characterized by small zero-grazing units. It is also an important trap crop used in the management of cereal stemborers in maize in the region. However, production of Napier grass in the region is severely constrained by Napier stunt disease. The etiology of the disease is known to be a phytoplasma, 16SrXI strain. However, the putative insect vector was yet unknown. We sampled and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…The primary mode of transmission of the disease is by vegetative propagation of infected planting material or by phloem-feeding insects belonging to the families Cicadellidae (leafhoppers), Delphacidae (planthoppers) and some psyllids (Psylloidea) [124,125]. Obura et al [126] identified Maiestas banda Kramer (Hemiptera:Cicadellidae) as a vector for Napier grass stunt disease phytoplasma in Kenya and Leptodelphax dymas and Exitianus spp. have been recorded in Ethiopia [127].…”
Section: Phytoplasma (Stunt) Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The primary mode of transmission of the disease is by vegetative propagation of infected planting material or by phloem-feeding insects belonging to the families Cicadellidae (leafhoppers), Delphacidae (planthoppers) and some psyllids (Psylloidea) [124,125]. Obura et al [126] identified Maiestas banda Kramer (Hemiptera:Cicadellidae) as a vector for Napier grass stunt disease phytoplasma in Kenya and Leptodelphax dymas and Exitianus spp. have been recorded in Ethiopia [127].…”
Section: Phytoplasma (Stunt) Diseasementioning
confidence: 99%
“…have been recorded in Ethiopia [127]. However, so far no vector has been identified in Uganda [126]. The vector-phytoplasma-host plant three-way interaction plays an important role in determining the spread of the disease [128].…”
Section: Phytoplasma (Stunt) Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Often the whole stool is affected with a complete loss in yield and eventual death. The Ns-disease has been reported in Kenya, Uganda, and Ethiopia, posing a serious negative effect on both dairy and cereal production in the predominantly mixed crop-livestock farming systems in the region (Jones et al 2004(Jones et al , 2007Nielsen et al 2007;Arocha et al 2009;Obura et al 2009). According to phylogenetic analysis of 16S rDNA sequences, the phytoplasmas associated with Ns-disease in Kenya and Uganda are classified into the 16SrXI group (Candidatus Phytoplasma oryzae or rice yellow dwarf) (Jones et al 2004;Nielsen et al 2007), while those occurring in Ethiopia are classified into the 16SrIII group (X-disease) (Jones et al 2007).…”
mentioning
confidence: 98%
“…Since there is no parasitic plant associated with Napier grass, the primary means of Ns-disease spread are the introduction of infected plant material (i.e., cane cuttings or clump splits) by farmers and/ or insect vectors carrying the phytoplasma. Recently, Obura et al (2009) tested the Ns-phytoplasma transmission ability of five leafhopper and three planthopper species and identified the leafhopper Maiestas banda (Kramer) [recently transferred from genus Recilia, Webb and Viraktamath (2009)] as a vector of Ns-phytoplasma in Kenya. However, despite that several different insect species are able to transmit the same kind of phytoplasma (Weintraub and Beanland 2006), little is known about fauna of leafhoppers/planthoppers on Napier grass in Africa.…”
mentioning
confidence: 99%